Think Piece: Building, repairing and maintaining trust in research relationships: towards an ethics of trust - Mathebula, Mikateko (Critical Studies in Teaching and Learning, 2025)
In this think piece, I ask what it takes for research relationships to be centred on trust. My reflections are divided into three sections in which I share some lessons learnt from various research projects. At the end of each section, I pose a series of interrelated questions about the values, principles and practices that are indispensable to building, repairing and maintaining trust in research relationships. To conclude, I outline how these reflections will be brought together in my keynote address.